Role of MicroRNAs in Mammalian Reproduction - Shavi; Saini, Sudha; Gupta, Tanya; Selokar, N L; Singh, M K (Animal Reproduction Update, 2023)
MicroRNAs are small, endogenous, non-coding RNA molecules that are around 19-25 nucleotides long. Most miRNAs are produced via transcription of DNA sequences into primary miRNAs, precursor miRNAs, and then mature miRNAs. These miRNA molecules base-pair to mRNAs to control gene expression post-transcriptionally. Mammalian genome now has over 2000 annotated miRNAs which are thought to influence one-third of the genes in the genome since each miRNA can regulate hundreds of target genes. miRNAs are involved in morphogenesis, tissue maintenance, cell development, differentiation, apoptosis, and metabolism etc. This review aims to summarize the current understanding of the role of miRNAs in various stages of mammalian reproductive biology and their involvement in reproductive disorders. We have also summarized the recent advances about miRNA and provide an updated overview of the literature, including the most recent and relevant studies.
Keywords: MicroRNAs; Reproduction; Oogenesis; Spermatogenesis